PEMBERDAYAAN KADER POSYANDU DALAM OPTIMALISASI PERTUMBUHAN DAN PERKEMBANGAN BALITA MELALUI PEMANFAATAN APLIKASI e-POSYANDU KESEHATAN (ePoK) DI KELURAHAN KAMPUNG BUGIS - Damayanti, Melly; Darwitri, Darwitri; HARDI, Nurul Aini Suria Saputri; Rawdatul Jannah (Bajang Institute, 2026)
The toddler period is a golden phase of child growth and development; therefore, optimal monitoring is required to prevent growth and developmental disorders. Posyandu cadres play an important role as the frontline in health monitoring at the community level. This community service program aimed to empower posyandu cadres in improving their knowledge and skills in monitoring and stimulating toddler growth and development through the use of the e-Posyandu Kesehatan (ePoK) application in Kampung Bugis Village, Tanjungpinang City in 2025. The target participants were 30 posyandu cadres from Kampung Bugis. The methods used included preparation, health education, hands-on practice in monitoring and stimulating growth and development, monitoring and mentoring, as well as evaluation. The results showed an improvement in cadres’ knowledge and skills in monitoring and stimulating toddler growth and development. A total of 90% of cadres achieved a high level of knowledge, and 86.7% demonstrated good skills. All toddlers attending the posyandu were monitored and stimulated by the cadres. Empowering posyandu cadres through the utilization of the ePoK application proved effective in optimizing growth and developmental monitoring. The sustainability of this program with the support of healthcare facilities and local government is essential to strengthen efforts in preventing growth and developmental problems in the community.